The Handbook of Social Work and Social Development in Africa - Butterfield, A. K. (Social Work/Maatskaplike Werk, 2018)
The Handbook of Social Work and Social Development in Africa, edited by Mel Gray, confirms my view on innovation and development and, for the first time, offers a storehouse of information on social work and social development in Africa.